Steam Boilers in Ready-Made Garments Industry in Bangladesh: Existing Scenario and Scope for Development - Siraj, Md Tanvir; Hasan, Md Mehedi; Ahmed, A N Faisal; Faruk, Faisal Bin; Ahmed, Md Foysal; Chowdhury, Md Kamrul Hasan; Ahmed, S M Faysal; Islam, Md Sohidul; Sefat E Nur, Kazi; Saeed, Syed Salman (Journal of Engineering Science, 2024)
Bangladesh's Ready-Made Garments (RMG) industry, historically prone to hazards including boiler explosions with numerous fatalities, has prompted the RMG Sustainability Council (RSC) to initiate boiler safety inspections. This study addresses the lack of empirical data on boiler operations in RMG factories, focusing on operational scenarios, risk factors, and remediation strategies. Conducted from March 2021 to March 2023, structured visual inspections across 1386 RMG factories assessed 2204 boilers. Key findings reveal that 34.99% of factories predominantly use a single boiler, 91.24% of boilers are government-registered, and the majority are imported (63.29%) with a steam generation capacity below 1,000 kg/hr (59.75%). Additionally, 63.11% were manufactured between 2010 and 2019, 79.63% burn fossil fuels, 54.60% are vertically oriented, and 82% use softened feedwater. The study also identifies 32 external risk factors across 11 categories, providing insights for decision-makers to enhance boiler operation safety and sustainability. By leveraging this inspection data, the research aims to bridge the empirical gap and offer a comprehensive understanding of the existing challenges in RMG boiler operations. Journal of Engineering Science 14(2), 2023, 89-105